To solve the quadratic equation \( 2x^2 - 5x - 3 = 0 \), we can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Here, \( a = 2 \), \( b = -5 \), and \( c = -3 \).
- First, calculate the discriminant \( b^2 - 4ac \):
\[ (-5)^2 - 4 \cdot 2 \cdot (-3) = 25 + 24 = 49 \]
- Now use the quadratic formula:
\[ x = \frac{-(-5) \pm \sqrt{49}}{2 \cdot 2} = \frac{5 \pm 7}{4} \]
- This gives us two solutions:
- For the positive case:
\[ x = \frac{5 + 7}{4} = \frac{12}{4} = 3 \]
- For the negative case:
\[ x = \frac{5 - 7}{4} = \frac{-2}{4} = -\frac{1}{2} \]
So, the solutions are:
Solution 1: \( x = 3 \)
Solution 2: \( x = -\frac{1}{2} \)
You might want to enter these solutions in the provided format.